New Zealand species of the genus Tripyla Bastian, 1865 (Nematoda: Triplonchida: Tripylidae). II: Two new, a known species and key to species - Zhao, Zengqi; Xu, Yumei (Zootaxa, 2013)
This paper describes three species of the genus Tripyla from New Zealand and provides a key to species based on the mor-phology of females. Tripyla daviesae sp. nov. is characterized by its short body length (L = 1143–1363 μm), relatively anterior vulva (V = 50–51%), and the length of the gubernaculum (13–17 μm). Tripyla tirau sp. nov. is characterized by its relatively posterior vulva (V = 55.5–59.5%), relatively short body length (930–1214 μm) and relatively short tail (c = 7.9–9.8). Tripyla affinis de Man, 1880 was recorded from New Zealand but without a detailed description which is pro-vided here. In addition, the phylogenetic relationships among the species were analyzed using data from the near full length small subunit (SSU) of the ribosomal rRNA genes, and confirmed that T. daviesae sp. nov. and T. tirau sp. nov. are distinct from all other species for which sequences are available.